Assessment of Serum Iron and Ferritin Status Among Day and Night Shift Workers: A Cross Sectional Study - Hamid, Saja Majid (American Journal of Biology and Natural Sciences, 2026)
Shift work is defined as a work pattern where workers perform tasks outside regular working hours. It has become an increasingly common phenomenon in various industries, many of which have been linked to burnout and identified as possibly detrimental to heart health. This study was conducted to explore the potential influence of the shift work on serum iron and ferritin. The current study included (80) participants consisting of (40) healthy day shift workers. In addition, (40) were night shift workers, spin react spin 120 system, completely automated biochemical analyzer (Germany) was used to determine the serum iron concentrations which assayed by using a commercial kit (BIO Research, Germany). Ferritin concentrations kits provided from (Abbott laboratories, USA) measured by automated Abbott Architect Ci4100 analyzer. The results of the current study, showed that the mean of serum iron levels were significantly lower (p≤0.05) in night shift workers (51.72±27.71 µg/dL) than day shift workers (74.17±15.50 µg/dL), while the ferritin levels didn’t show significant differences between day and night shift workers. Depending on the years of work. The serum iron exhibited a significant decrease (p≤0.05) among workers with more than 5 years of exposure (42.56±23.01 µg/dL) compared to those with less than 5 years (80.82±22.38 µg/dL), while serum ferritin didn’t show significant differences. The night shift work was associated with reduced serum iron concentrations compared with day work. Although ferritin concentrations tended to be higher with prolonged night work no statistically significant differences were observed.